PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS WEB UNTUK MENGUATKAN LITERASI NUMERASI SISWA SD - Isnaeni Maryam (Joyful Learning Journal, 2026)
This study aims to develop web-based learning media and to determine whether the media is suitable for strengthening the numeracy literacy skills of elementary school students. This research is a development research (R&D). This study took 27 students of class VA Muhammadiyah Bayan Elementary School as subjects. Data collection, researchers used validation sheets, student response questionnaires, and numeracy literacy test questions as instruments. After the data were collected, researchers used quantitative descriptive to analyze the data. Web-based learning media was developed through 4D design (Define, Design, Develop, Disseminate). The validity test of the learning media showed a score of 87% with very valid criteria for the material aspect, and 85% with very valid criteria for the media aspect. Meanwhile, based on the results of student responses, the ease aspect reached 87%, interestingness 90%, and usefulness 86%. The average score for numeracy literacy skills was 81 with a completion percentage of 82%. Thus, it can be said that the developed web learning media is valid, practical, and effective. So it is suitable for strengthening students' numeracy literacy.